INFLUENCE OF DISTANCE BETWEEN A RETAINING WALL AND THE EXISTING BUILDING ON STRESS-STRAIN STATE OF THE SYSTEM «RETAINING STRUCTURES – SOIL MASSIF» (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of work research of engineering protective structures in a densely built–up area with difficult engineering–geological conditions have been presented. The modeling of the geotechnical problem of deep excavation protection using a three-tier retaining wall has been performed.  The task of mutual influence of existing building and deep excavation with the change of distance between them is solved. The grafs of displacement’s dependence several tiers of retaining walls from the distance to an existing building have been presented. According to these data, a plot of the dependence of displacements of separate tiers of retaining walls from the distance to an existing building is constructed. The problem is solved by the finite element method using a nonlinear model of a solid soil environment. The character of the formation of zones of potential slip surface slope is revealed. The dependence of bending moments of the retaining walls from the distance to the existing building is shown. A safe location of an existing building to a deep excavation has been substinated.
Keywords: numerical modeling; engineering protective structures; finite element method; horizontal displacements; bending moments